Quality Changes and Discoloration of Basa (Pangasius bocourti) Fillet during Frozen Storage - Pornpimol Sriket; Thamarak La-ongnual (Journal of Chemistry)
Physicochemical changes of Basa fish (Pangasius bocourti) fillet during frozen storage at −20°C for 0–20 weeks were studied. The content of thiobarbituric acid reactive substances (TBARS) of fish samples suddenly increased when the samples were stored longer than 8 weeks (p<0.05). The increase in TBARS value of the fish fillet was concomitant with the increase in b∗ value (yellow color). Marked decreases in Ca2+-ATPase activity, sulfhydryl content, and protein solubility of the fish fillet after 8 weeks of storage were observed. Those decreasing values were well correlated with the increasing of disulfide bond content and surface hydrophobicity content (p<0.05). Increases in shear force of fish meat during storage were also observed (p<0.05). The results indicated that frozen storage at −20°C affected on Basa fillet qualities, especially after 8 weeks of storage. These data could be useful for consumer and food industry.